The Influence of the Role Play Method Based on the Group Investigation Model on the Learning Motivation of Maharah Kalam - Thalia Tanzila; Nurrokhmatulloh; Syarifuddin (Raja Zulkarnain Education Foundation, 2026)
The role play method based on the group investigation model is a learning method that involves students to play a role as a certain character in a situation. Students can improve their critical thinking skills, communication, collaboration, creativity, and empathy through the stages of identifying topics and dividing students into groups, planning tasks to be studied, carrying out investigations, preparing final reports, presenting final reports, and evaluation. This study aims to describe the effect of the group investigation-based role playing learning model on the motivation to learn maharah kalam. This study uses a non-experimental quantitative approach with a correlational design. The study population was 97 students of MA Al-Hikmaturrohmaniyah Sukorejo Pasuruan who followed the group investigation-based role playing learning model. The research sample was determined using a purposive sampling technique so that 30 grade XII students were obtained as respondents. The research data were collected using a Likert scale questionnaire consisting of 20 statement items, namely 10 items for variable X and 10 items for variable Y. The data were analyzed using a nonparametric inferential statistical procedure, namely Spearman's rank order correlation. This procedure was chosen from non-ordinal data and sampling did not use simple random. The results of the study found a value of r = 0.597 so that the determination (R²) of 0.3564 indicates that variable X contributed 35.64% to the motivation to learn maharah kalam for grade XII students. Thus, the application of the role play model based on group investigation contributes to increasing students' learning motivation, active involvement, and courage to speak in learning maharah kalam.